Annual Report of the Librarian of Congress, 1987, for the Fiscal Year Ending September 30, 1987 - Library of Congress, Washington, DC.; Library of Congress, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Fiscal year activities are summarized for seven organizational areas of the Library of Congress: (1) Administration--Office of the Librarian and Management Services; (2) National Programs--American Folklife Center, Children's Literature Center, Educational Liaison Office, Exhibits Office, Federal Library and Information Center Committee, Information Office, National Library Service for the Blind and Physically Handicapped, and Publishing Office; (3) Congressional Research Service, including examples of selected major issues dealt with in the 100th Congress; (4) Processing Services--acquisitions and overseas operations, bibliographic products and services, cataloging, networking, and staff activities; (5) Research Services--acquisitions, management of collections, preservation, services to readers, automation, public programs, publications, administration, and basic workload; (6) Law Library--service to Congress, service to government and other noncongressional users, special projects and publications, collection development and maintenance, and personnel; and (7) Copyright office--changing technologies, Copyright Office operations, Copyright Office regulations, legislative developments, judicial developments, and international meetings. Also included are lists of library officers and an organization chart. The appendixes present statistics on various activities as well as information on legislation; exhibits; concerts, lectures, and other programs; Library of Congress publications; and litigation. (MES)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, DC 20402.
ERIC Note: For the 1986 report, see ED 286 534.
Microfiche.
Keywords: Annual Reports; Cataloging; Copyrights; Federal Programs; Information Science; Law Libraries; Library Services; Library Statistics; National Libraries; Program Descriptions; Research Libraries; Library of Congress; Congressional Research Service -- Copyright Office; Reports, Descriptive